Beliefs and conceptions. Complementary perspectives - Fuensanta Hernández Pina; Javier J. Maquilón Sánchez (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The beliefs and conceptions of teaching and learning held by teachers is a research topic which could mean a step forward in our understanding of important factors for improving the quality of Education. For over two decades, a number of researchers have achieved results through studies which offer a corpus of solid knowledge about beliefs and conceptions of teaching and learning which has resulted in establishing new andinteresting interpretations of that relationship. In this paper, we present the ideas about beliefs and conceptions held by a group of researches about teaching and learning.